The Motivating Role of Sentiment in ESG Performance: Evidence from Japanese Companies - Ngoc Bao Vuong; Yoshihisa Suzuki (East Asian Economic Review (EAER), 2021)
The paper investigates investor sentiment's role in boosting Japanese companies to enhance their environmental, social, and corporate governance (ESG) performance. Using ESG scores of 367 firms between 2005 and 2019 from the ASSET4 database, we find that negative sentiment in the previous year, both firm and market level, can be a stimulation for the company's commitments to its ESG activities next year. Notably, the moderating effect of the business sector and economic cycle on the sentiment-ESG inference are detected in our study differentiating between corporate and market sentiment, which have never been reported before. In detail, we discover that the impact of firm-specific sentiment is less pronounced for high-sensitive ESG firms. On the other hand, the driving force of market sentiment on corporate social behaviors weakens when economic recessions happen. Our results are robust after controlling for potential endogeneity issues and using alternative proxies for market sentiment.
Keywords: G30; G40; M14; 330; Firm-specific and Market Sentiment; Corporate Social Responsibility; ESG Performance; Business Sector; Economic Cycle